Infrared spectra and structures of protonated amantadine isomers: detection of ammonium and open-cage iminium ions. Issue 26 (24th June 2022) - George, Martin Andreas Robert; Dopfer, Otto
Abstract : The two isomers of the pharmaceutically active AmaH + ion identified by IR spectroscopy are the canonical ammonium isomer (I ) formed by protonation at the NH2 group and a protonated bicyclic iminium ion (II ) formed by ionization of Ama followed by cage opening and H addition. Abstract : The protonated form of amantadine (1-C10 H15 NH2, Ama), the amino derivative of adamantane (C10 H16, Ada), is a wide-spread antiviral and anti-Parkinsonian drug and plays a key role in many pharmaceutical processes. Recent studies reveal that the adamantyl cage (C10 H15 ) of Ama can open upon ionization leading to distonic bicyclic iminium isomers, in addition to the canonical nascent Ama + isomer. Herein, we study protonation of Ama using infrared photodissociation spectroscopy (IRPD) of Ar-tagged ions and density functional theory calculations to characterize cage and open-cage isomers of AmaH + and the influence of the electron-donating NH2 group on the cage-opening reaction potential. In addition to the canonical ammonium isomer (AmaH + (I )) with an intact adamantyl cage, we identify at least one slightly less stable protonated bicyclic iminium ion (AmaH + (II )). While the ammonium ion is generated by protonation of the basic NH2 group, AmaH + (II ) is formally formed by H addition to a distonic bicyclic iminium ion produced upon ionization of Ama and subsequent cage opening.